Effect of material parameter on mixed convective fully developed micropolar fluid flow in a vertical channel. Issue 6 (19th April 2021) - Kalyan, Shreedevi; Sharan, Ashwini; S, Jyothi
Abstract: In this study, the effect of material parameter on the mixed convective fully developed micropolar fluid flow in a vertical channel has been analyzed. By considering appropriate boundary and interface conditions, the coupled nonlinear equations are solved analytically. The analytical results are plotted for various important parameters. It is found that an increase in the material parameter enhances the microrotation velocity and decreases the fluid velocity, and the results are shown graphically.